2002
DOI: 10.1038/sj.cr.7290137
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a mouse liver-specific gene mfrep-1, upregulated in liver regeneration

Abstract: Human fibrinogen-related protein-1/liver fibrinogen-related protein-1 (HFREP-1/LFIRE-1), a liverspecific protein, is a member of fibrinogen superfamily that exerts various biological activities. However, the function of HFREP-1/LFIRE-1 in liver remains unknown. Here we isolated its mouse ortholog gene-mouse fibrinogen-related protein-1 (mfrep-1), which encoded 314 amino acids, exhibiting 80.4% similarity to HFREP-1/LFIRE-1. Northern blot analysis revealed that 1.2-kb mfrep-1 mRNA was detected selectively in mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 25 publications
2
30
0
Order By: Relevance
“…Research has indicated that FGL1 exerts multiple hepatic protective functions by promoting hepatocyte proliferation and decreasing the rate of apoptosis. A previous study indicated that administration of FGL1 to animals following D-Gal treatment significantly reversed liver injury by promoting hepatocyte proliferation and reducing liver apoptosis, while knockdown of endogenous FGL1 expression exacerbated liver injury (22,23). Concurrent with these results, the present study indicated that the level of FGL1 was enhanced 72 h following the induction of liver injury, indicating that FGL1 was activated upon induction of spontaneous liver regeneration.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Research has indicated that FGL1 exerts multiple hepatic protective functions by promoting hepatocyte proliferation and decreasing the rate of apoptosis. A previous study indicated that administration of FGL1 to animals following D-Gal treatment significantly reversed liver injury by promoting hepatocyte proliferation and reducing liver apoptosis, while knockdown of endogenous FGL1 expression exacerbated liver injury (22,23). Concurrent with these results, the present study indicated that the level of FGL1 was enhanced 72 h following the induction of liver injury, indicating that FGL1 was activated upon induction of spontaneous liver regeneration.…”
Section: Discussionsupporting
confidence: 73%
“…FGL1 (also termed FREP1 or hepassocin) is a protein secreted by hepatocytes, which is a member of the fibrinogen family (20). Studies have shown that FGL1 is implicated in liver injury as a mitogenic growth factor and may facilitate damaged liver tissue regeneration and downregulate the expression of proapoptotic factors (21)(22)(23). In the present study, it was hypothesized that intravenous transplantation of BMSCs may increase the expression of FGL1 in the injured rat liver and rescue the liver following acute injury.…”
Section: Introductionmentioning
confidence: 89%
“…HPS was induced 2 h after a 70% hepatectomy of mouse livers, and the second peak arrived 24 h later. The expression of HPS remained high until 72 h later and declined to the basal level thereafter (3), suggesting that HPS may function as a regulator of cell growth in liver regeneration. Functionally, HPS was initially described as generating mitogenic activity on isolated hepatocytes, whereas it did not promote DNA synthesis in non-liver cell lines in vitro.…”
mentioning
confidence: 94%
“…The position within the human genome is mapped to chromosome 8p22-21. 3. It has been reported that the expression of HPS mRNA was detected mainly in murine livers.…”
mentioning
confidence: 99%
See 1 more Smart Citation